(untitled) (Estudios humanísticos. Geografía, historia y arte, 2021)
Our purpose in this work is to put forward certain factors of analysis which have been taken from the cultural ecology and applied to the gipsy community, particularly to the one living in León. Through adaptation and competition, new aspects of the relationships between these two communities come out; our intention is to describe them extensively